2006 Canadian Conference on Electrical and Computer Engineering 2006
DOI: 10.1109/ccece.2006.277332
|View full text |Cite
|
Sign up to set email alerts
|

Towards the System-on-Chip Realization of a Sensorless Vector Controller with Microsecond-order Computation Time

Abstract: Abstract-The aim of this research is to implement sensorless vector control algorithms on a single, eventually reconfigurable, chip, with a computation timing constraint of, at most, 1-6 microseconds, and a concern for implementation cost. In this article, we discuss the implementation problems and tradeoffs involved in meeting these goals on Field-Programmable Gate Arrays (FPGAs). To be able to fit a complete induction motor vector controller on a single, inexpensive FPGA chip, we estimate the area/time requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Moreover, it shows that this work can accomplish the transformation within 2 clock cycles which means that the execution time is as low as 50 ns in 40 MHz frequency. The execution time required in this proposed solution is much smaller than research from [ 18 20 ]. The proposed design required no memory resources as required in [ 20 ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, it shows that this work can accomplish the transformation within 2 clock cycles which means that the execution time is as low as 50 ns in 40 MHz frequency. The execution time required in this proposed solution is much smaller than research from [ 18 20 ]. The proposed design required no memory resources as required in [ 20 ].…”
Section: Resultsmentioning
confidence: 98%
“…The research proposed the idea of realizing a high-speed current dq PI controller into FPGA but did not show any results [ 17 ]. Beguenance et al showed the hardware implementation of a current controller in a FOC PMSM drive [ 18 ]. The research implemented the PI controller along with a decoupling method for controlling dq -axis current of a FOC PMSM drive.…”
Section: Introductionmentioning
confidence: 99%